The Conscious and Unconscious Power in Pedagogy of Creative Writing: Liberation of Self (LSP International Journal, 2017)
This paper discusses the idea of creative writing as a stimulant for higher order thinking. In doing so, it examines the relationship between creative thinking and writing processes. Therefore, in elaborating the term creative thinking, the paper discusses in the light of Sigmund Freud’s psychoanalysis theory – the unconscious mind. Under the influence and guidance of our unconscious mind, a liberating writing process occurs in a creative form. During this writing process, we develop a new identity as a result of the production of language. In which, this “new identity” has no influence or power over reader’s knowledge, however noble the writing can be.